Job refusal among people with schizophrenia in Hospital Permai, Johor Bahru / John Chieng Kwang Chong - John, Chieng Kwang Chong (2016)
The goals for treating patients with schizophrenia are now not only limited to symptoms reduction and relapse prevention. Functional recovery is equal, if not the most, important in treating patients with schizophrenia. Functional recovery encompassed: symptoms stability, independent living, work functioning and social functioning. Method This study uses Explanatory Sequential Mixed-method design. It involved both quantitative and qualitative statistical analysis. In the first part, the quantitative approach, 96 people with schizophrenia referred to Hospital Permai’s OT for supported employment were assessed quantitatively for employment characteristics (duration of employment, the number of previous jobs and longest job) and clinical characteristics using RSES (Rosenberg self-esteem scale), QUAD (Questionnaires on Anticipated Discrimination), PANSS (Positive and Negative Symptoms Scale), and GASS (Glassgow Antipsychotic side effect scale). In the second part, the qualitative approach, thematic analysis of from nine individual interviews and two focus groups interviews consisting of thirteen employment specialists were carried out. The results and findings from these two parts were integrated and interpreted together. vi Result and Findings From the Part 1 of the study, the prevalence of people with Schizophrenia that refused to work after referral to the Supported Employment program is 24.0%. The study also found a significant association between ‘Duration of unemployment’ and ‘Job refusal’ with P=0.031, OR =1.018 (95% CI=1.002 - 1.035). Part 2 of the study identified several themes related to job refusal among people with schizophrenia namely; Cognitive Deficit Secondary to Schizophrenia, Side Effects of Medications, Easily Contented, Lack of Drive, Stigma (Internal and External), Subpar Work Performance, Fear of Relapse, Somatic Symptoms, Inadequate Social Skills, Dependency on Family, Family as a Barrier, Stigma from healthcare professionals, stigma from employers, and Stigma from community. The mixed method employed by this study found that the reasons for job refusal are related to anxiety. This anxiety could have been heightened by the long duration of unemployment. Our study also postulates that these anxieties are caused by poor work performance secondary to cognitive deficit associated with schizophrenia, inadequate social skills, and internalized stigma and stigma from general population. We also found that the patients’ family may also act as a barrier to employment by being over-involved in patients’ illness. Conclusion All in all, there should be close collaboration between all the services in mental health service, with focus on psycho-education and increasing contact between community and people with mental illness to help them to manage themselves better to return to function. We should focus not only on symptoms remission, but to start managing them holistically and aim for functional recovery.